2017
DOI: 10.1200/jco.2017.35.15_suppl.3005
|View full text |Cite
|
Sign up to set email alerts
|

CX-1158-101: A first-in-human phase 1 study of CB-1158, a small molecule inhibitor of arginase, as monotherapy and in combination with an anti-PD-1 checkpoint inhibitor in patients (pts) with solid tumors.

Abstract: 3005 Background: Arginase is secreted by myeloid-derived suppressor cells (MDSCs) and polymorphonuclear cells (PMNs) in the tumor microenvironment, depleting arginine, an amino acid required for T-cell activation and proliferation. CB-1158 is an oral small molecule inhibitor of arginase. CB-1158 reverses PMN- and MDSC-mediated suppression of T-cells in ex vivo human models, and increases plasma and tumor arginine levels in mouse syngeneic tumor models leading to increased pro-inflammatory markers and activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Keeping this notion in mind, Calithera has developed the arginase inhibitor CB‐1158 (Figure ) with the overall intent of preventing arginine depletion in the local tumor microenvironment. Pre‐clinical data has demonstrated that CB‐1158 reverses the capacity of polymorphonuclear cells and myeloid‐derived suppressor cells to inhibit T‐cell activation and proliferation ex‐vivo by preventing arginine depletion . Moreover, pre‐clinical data has demonstrated that CB‐1158 increases plasma and tumor arginine levels in mouse syngeneic tumor models, resulting in increased pro‐inflammatory markers and activated CD8 T‐cells in the tumor .…”
Section: Small Molecule Inhibitors: Targeting Both Cancer and Immune mentioning
confidence: 99%
See 2 more Smart Citations
“…Keeping this notion in mind, Calithera has developed the arginase inhibitor CB‐1158 (Figure ) with the overall intent of preventing arginine depletion in the local tumor microenvironment. Pre‐clinical data has demonstrated that CB‐1158 reverses the capacity of polymorphonuclear cells and myeloid‐derived suppressor cells to inhibit T‐cell activation and proliferation ex‐vivo by preventing arginine depletion . Moreover, pre‐clinical data has demonstrated that CB‐1158 increases plasma and tumor arginine levels in mouse syngeneic tumor models, resulting in increased pro‐inflammatory markers and activated CD8 T‐cells in the tumor .…”
Section: Small Molecule Inhibitors: Targeting Both Cancer and Immune mentioning
confidence: 99%
“…Pre‐clinical data has demonstrated that CB‐1158 reverses the capacity of polymorphonuclear cells and myeloid‐derived suppressor cells to inhibit T‐cell activation and proliferation ex‐vivo by preventing arginine depletion . Moreover, pre‐clinical data has demonstrated that CB‐1158 increases plasma and tumor arginine levels in mouse syngeneic tumor models, resulting in increased pro‐inflammatory markers and activated CD8 T‐cells in the tumor . The pharmacokinetics and pharmacodynamics of CB‐1158 are currently being explored in a Phase 1 study of solid tumors (Table ).…”
Section: Small Molecule Inhibitors: Targeting Both Cancer and Immune mentioning
confidence: 99%
See 1 more Smart Citation
“…Parlati and colleagues reported (Steggerda et al, 2016) the biological activities of CB-1158 (Calithera Biosciences), a selective small-molecule inhibitor of both arginase 1 and 2 with a biochemical half maximal inhibitory concentration (IC 50 ) = 0.10-0.3 mM. In murine syngeneic colon and melanoma models, the inhibitor increased plasma and tumor arginine levels, increased pro-inflammatory markers, activated CD8 + T cells in the tumor, and possessed synergistic activity when combined with an anti-PDL-1 mAb, gemcitabine, or adoptive T cell therapy (Steggerda et al, 2016;Papadopoulos et al, 2017). CB-1158 is currently in a phase 1 clinical study to evaluate safety and tolerability as a monotherapy and in combination with anti-PD-1 in patients with solid tumors (Papadopoulos et al, 2017).…”
Section: Future Directionsmentioning
confidence: 99%
“…In murine syngeneic colon and melanoma models, the inhibitor increased plasma and tumor arginine levels, increased pro-inflammatory markers, activated CD8 + T cells in the tumor, and possessed synergistic activity when combined with an anti-PDL-1 mAb, gemcitabine, or adoptive T cell therapy (Steggerda et al, 2016;Papadopoulos et al, 2017). CB-1158 is currently in a phase 1 clinical study to evaluate safety and tolerability as a monotherapy and in combination with anti-PD-1 in patients with solid tumors (Papadopoulos et al, 2017). The only reported potent small-molecule arginase 1 inhibitors are analogs of 2(S)-amino-6-boronohexanoic acid, with low nanomolar binding affinity against human arginase I.…”
Section: Future Directionsmentioning
confidence: 99%